Using the caffeine breath test to study drug metabolism in protein-energy malnourished children - Oshikoya, Kazeem Adeola (2014)
Malnutrition is a global health problem that affects infants and young children. It is frequently associated with infections and commonly affects children in developing countries. Malnutrition is the cellular imbalance between the supply of energy from macronutrients and micronutrients and the demand of the body for them in order to achieve normal growth, maintenance, and specific functions. Underweight (mild to moderate) and marasmus, marasmic-kwashiorkor, and kwashiorkor (severe) are the spectrum of malnutrition.